FORMULASI STRATEGI PERUSAHAAN STUDI PADA PT KAYAN PUTRA UTAMA COAL - , Raditya Kusuma Putra, Dr. Goedono, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The theme in the research conducted by the author outlines the formulation of corporate strategy. Object of research is acompany which is engaged in coal mining industry located in the village of East Kalimantan, Langap, Malinau. The study uses a case study approach and elaborated descriptively. Results of the formulation of corporate strategy put forward by the authors is related diversification strategy. Studies conducted using several measuring tools to obtain information needed in the formulation of a company's strategy. Measuring instrument that is used among other Likert scale used to measure the strengths, weaknesses, opportunities and threats faced by the company. Other measuring tools such as SWOT matrix and the matrix SPACE is also used as an additional tool in writing. The entire gauge is filled by the authorities PT Putra Kayan Main Coal and processed by the author so that the conclusion strategy options that can be taken by the author. The results of research and discussion to provide information for the author. Broadly speaking, the authors conclude on the value chain analysis and analysis of key success of the company, PT Putra Kayan Main Coal has the distribution channels and good procurement procedures. The results of the SWOT analysis and matrix analysis shows SPACE PT Putra Kayan Main Coal has the ability to grow in terms of operational efficiency and managerial performance improvements and have the ability in terms of taking the opportunities that exist within the industry and can avoid the threat from outside. Kayan PT Putra Main Coal industry moves at a pretty interesting and has the potential to grow. So that the whole strength of companies can be used optimally. The products produced by PT Putra Kayan Main Coal is unique and as a base material for other industrial users, and therefore related diversification strategy can be applied such as opening the energy companies are expected to expand and increase market penetration into other industries.